2015
DOI: 10.4081/mrm.2015.356
|View full text |Cite
|
Sign up to set email alerts
|

Effects on asthma and respiratory allergy of Climate change and air pollution

Abstract: The major changes to our world are those involving the atmosphere and the climate, including global warming induced by anthropogenic factors, with impact on the biosphere and human environment. Studies on the effects of climate changes on respiratory allergy are still lacking and current knowledge is provided by epidemiological and experimental studies on the relationship between allergic respiratory diseases, asthma and environmental factors, like meteorological variables, airborne allergens and air pollution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 32 publications
0
15
0
3
Order By: Relevance
“…For example, seasonal differences in pollen production are linked to seasonal trends in asthma attacks, and all 4 study groups had significantly positive allergen tests. However, the present study also revealed a gradual decrease in the proportion of seasonal asthma attacks, which may be related to the increased suspension of airborne particles containing allergens, a prolonged pollen season as a consequence of global warming, [ 6 ] and modification of the allergen by air pollutants. [ 7 ] Moreover, we observed an increasing prevalence of allergic rhinitis, which agrees with the increasing prevalence of AA in a previous report.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…For example, seasonal differences in pollen production are linked to seasonal trends in asthma attacks, and all 4 study groups had significantly positive allergen tests. However, the present study also revealed a gradual decrease in the proportion of seasonal asthma attacks, which may be related to the increased suspension of airborne particles containing allergens, a prolonged pollen season as a consequence of global warming, [ 6 ] and modification of the allergen by air pollutants. [ 7 ] Moreover, we observed an increasing prevalence of allergic rhinitis, which agrees with the increasing prevalence of AA in a previous report.…”
Section: Discussionmentioning
confidence: 82%
“…Allergic asthma is usually induced by specific environmental factors or foods during summer or autumn. With the rapid urbanization and industrialization of China, many serious air pollution problems have emerged, [ 6 ] and air pollutants have become new AA allergens, which has induced changes in the clinical features of AA. For example, seasonal differences in pollen production are linked to seasonal trends in asthma attacks, and all 4 study groups had significantly positive allergen tests.…”
Section: Discussionmentioning
confidence: 99%
“…Exposure to VOCs is associated with respiratory disorders like asthma, bronchitis and chronic obstructive pulmonary disease (COPD) 6,7 . COPD occurs due to the limitation of the airflow caused by the inflammation on the lungs resulting from the inhalation of harmful gas and particles 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Астма належить до індикаторних захворювань, які певною мірою можуть бути залежними від стану навколишнього середовища, зокрема від забрудненості повітря хімічними та біологічними полютантами, які належать до екзогенних факторів ризику розвитку цього захворювання. Зростанню забрудненості атмосферного повітря сприяють прогресивна урбанізація, недостатня модернізація технологічного обладнання підприємств, яка повинна була б сприяти зменшенню викидів полютантів у зовнішнє середовище, збільшення промислових потужностей, які прямо або опосередковано здатні впливати на поширеність та захворюваність БА [3]. Відомо, що Одеська область -це регіон, який, завдяки вигідному географічному розташуванню, виконує роль важливого транспортно-розподільчого коридору, та-кож характеризується високим рівнем розвитку сільського господарства та промисловості.…”
unclassified
“…За даними наглядових служб, понад 3 тисячі підприємств у нашому регіоні впливають на стан атмосферного повітря. Незважаючи на те, що Одеський регіон -це курортна зона на березі Чорного моря, він має високе антигенне навантаження, яке постійно впливає на імунну систему людини та здатне індукувати алергічне запалення дихальних шляхів внаслідок поєднаного впливу різноманітних техногенних забруднювачів [3,4].…”
unclassified